Anolyte recycling enhanced bioelectricity generation of the buffer-free single-chamber air-cathode microbial fuel cell. (November 2017) - Ren, Yueping; Chen, Jinli; Shi, Yugang; Li, Xiufen; Yang, Na; Wang, Xinhua
Highlights: Anolyte recycling enhanced HCO3 − accumulation in the buffer-free anolyte. Anolyte recycling eliminated the anolyte acidification in buffer-free MFC. Anolyte recycling dramatically improved the electric power of buffer-free MFC. Anolyte recycling induced the growth of Geoalkalibacter genus in anode biofilm. Abstract: Anolyte acidification is an inevitable restriction for the bioelectricity generation of buffer-free microbial fuel cells (MFCs). In this work, acidification of the buffer-free KCl anolyte has been thoroughly eliminated through anolyte recycling. The accumulated HCO3 − concentration in the recycled KCl anolyte was above 50 mM, which played as natural buffer and elevated the anolyte pH to above 8. The maximum power density ( P max ) increased from 322.9 mW m −2 to 527.2 mW m −2, which is comparable with the phosphate buffered MFC. Besides Geobacter genus, the gradually increased anolyte pH and conductivity induced the growing of electrochemically active Geoalkalibacter genus, in the anode biofilm. Anolyte recycling is a feasible strategy to strengthen the self-buffering capacity of buffer-free MFCs, thoroughly eliminate the anolyte acidification and prominently enhance the electric power.